Nonlinear Angular and Polarization-Dependent Reflectance Sensitivity in MAPbI₃ Thin-Film Structures: Thickness-Tuned TiO₂ Interlayer Effects - Abdullah Lateef (Physical Sciences, Life Science and Engineering, 2025)
This study presents a theoretical investigation of the angular and polarization-dependent reflectance sensitivity of MAPbI₃-based thin-film structures using the Transfer Matrix Method (TMM). Two configurations were considered: a single-layer structure and a bilayer structure incorporating a TiO₂ interlayer . The analysis was performed within the 300–800 nm spectral range under oblique incidence conditions. The results show that the reflectance sensitivity exhibits a clear nonlinear dependence on the angle of incidence. Under TE polarization, the sensitivity increases significantly with angle and reaches its maximum at 60°, indicating strong angular amplification driven by interference-induced phase modulation. In contrast, TM polarization demonstrates a gradual reduction in sensitivity, accompanied by a sign reversal at higher angles due to impedance matching effects near Brewster-related conditions. The introduction of a TiO₂ interlayer preserves the overall angular trend while enabling moderate structural tuning. Thickness optimization reveals polarization-dependent optimal values, with peak TE sensitivity obtained near 80 nm and peak TM sensitivity around 50 nm. However, quantitative comparison between single- and bilayer configurations confirms that angular control plays a more dominant role in sensitivity enhancement than thickness adjustment alone. Overall, the findings highlight the effectiveness of polarization-engineered angular modulation as a practical approach for enhancing reflectance-based sensing performance in perovskite multilayer systems, offering simplified design guidelines for angle-selective photonic coatings and optical sensors.